2002
DOI: 10.1039/b202203f
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of anions and ligands on the nature and reducibility of NiOx/Al2O3 catalysts prepared by impregnation

Abstract: When NiOx/Al2O3 catalysts (Ni wt% = 1.5) are prepared by impregnation using [NiL2(H2O)2]X2 as precursors (L = diamine, X = Cl- or NO3-), a supported oxidic or metallic phase can be selectively obtained after thermal treatment in N2 depending on the nature of the ligand and counter anion; the oxidic phase can be reduced at a lower temperature than the classical nickel aluminate phase obtained from [Ni-(H2O)6](NO3)2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…[50,52,53] Supramolecular adducts involving this pattern have been found in situations reminiscent of our case, for instance, between the aqua ligands of the complex [Ni(H 2 O) 6 ] 2 + and oxygen atoms of crown ethers. [54] Similar bonds were recently evidenced spectroscopically in a study on the interaction of [Ni(en) 2 (H 2 O) 2 ] 2 + with an alumina surface, [55] and cooperative effects quite similar to our model were proposed by Taylor et al for the adsorption of cobalt neocuproine complexes on silica. [56] The next step would be to identify the nature of the surface oxygen atoms that act as hydrogen-bond acceptors.…”
Section: à2supporting
confidence: 69%
“…[50,52,53] Supramolecular adducts involving this pattern have been found in situations reminiscent of our case, for instance, between the aqua ligands of the complex [Ni(H 2 O) 6 ] 2 + and oxygen atoms of crown ethers. [54] Similar bonds were recently evidenced spectroscopically in a study on the interaction of [Ni(en) 2 (H 2 O) 2 ] 2 + with an alumina surface, [55] and cooperative effects quite similar to our model were proposed by Taylor et al for the adsorption of cobalt neocuproine complexes on silica. [56] The next step would be to identify the nature of the surface oxygen atoms that act as hydrogen-bond acceptors.…”
Section: à2supporting
confidence: 69%
“…Besides metal precursor salts, organic complexing agents such as citric acid and nitrilotriacetic acid are often added to impregnation solutions. [9][10][11] Different metal chelate complexes can thus be formed in the impregnation solution depending on pH and concentration. Moreover, it has been shown that pH gradients can occur inside catalyst bodies after impregnation, which can be expected to influence the interaction between metal-ion complexes and the support surface.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent treatments are detailed in Sect. 3 6 ](NO 3 ) 2 following the procedure described in [6].…”
Section: Catalysts Preparationmentioning
confidence: 99%
“…Another route consists in changing the nickel precursor to salts containing nitrates and ligands such as ethylenediamine (en, NH 2 -CH 2 -CH 2 -NH 2 ), and decomposing them in argon [3,6,7]. During heating, nitrates oxidize the en ligands but not completely.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation